Race and gender as factors of students' survival to the Fifth Form in Trinidad and Tobago - Jules, Vena (Institute of Social and Economic Research, UWI, 1991)
This study raises questions of student survival both at the level of the individual and the race group. The specific questions addressed were: 1) Who, in terms of race, gender and education region, survived the guaranteed five years; 2) What is the survival rate of students from Fourth to Fifth Form? 3) How do those who survive the Fifth Form perceive school? and 4) How are they helped with school work outside of school? A questionnaire was administered to a sample of 2,198 students, of whom 1,744 completed it. Results of the data analysis showed that overall 1) students of all major race groupings survive the guaranteed five years equally well, and that 2) while students may have entered secondary school with varying perceptions of it, once there, there is no significant difference in their perceptions and expectations of secondary schooling that can be related to race. Significant variations were found in other categories--school locality or education region, occupation of parents, and sex of student
Keywords: Gender analysis